Tax Progressivity and the Trade Union's Fallback-Option - Stefan Boeters (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
When we analyse the labour market consequences of labour tax reforms in a model of firm-union wage bargaining, minor changes in the formulation of the union`s fallback option can have drastic effects. This paper compares two variants of the model in which either workers have no reemployment opportunity or the probality of employment in another sector is determined by the overall unemployment rate. It is argued both on analytical and numerical grounds that the second alternative is the only plausible one. This conclusion is confirmed by an explicit integration of workersinter-sectoral mobility into the model.
Keywords: H20; J51; 330; labour taxation; tax progression; tax reform; trade unions; unemployment; labour mobility; Lohnsteuer; Steuerprogression; Steuerreform; Steuerwirkung; Theorie der Arbeitslosigkeit; Lohnverhandlungstheorie; Arbeitsmobilität; Theorie